The Impact of Government Regulations and Green Marketing Mix on Green Purchase Behaviour in Pakistan - Ahmed Ansari, Hafiz Waqas (2023)
Governments and organisations are paying more attention to green purchase behaviour (GPB) since there is a dearth of understanding, especially in consumer markets like Pakistan. The literature has shown that significant predictors of GPB include internal and external factors. So, the study aims to investigate the influence of contextual factors (government regulations, green product, green price, green place, and green promotion) and attitudinal factors (attitude towards green purchase) on GPB through a research framework based on the attitude-behaviour-context (ABC) theory and the stimulusorganism-response (SOR) model. Moreover, the relationship between attitude towards green purchase and GPB has been investigated with the moderation of green trust. This study is quantitative and descriptive, using convenience sampling and the survey method for data collection from the buyers of energy-efficient electric appliances in the top ten most populated cities in Pakistan. A total of 500 questionnaires were distributed online, of which 387 has used. Using SmartPLS3 software for PLS-SEM to statistically analyse hypothesised paths, the results revealed that government regulations, green product, and green price have a direct and indirect significant relationship through the mediation with GPB. The green promotion has not directly affected GPB but has indirectly through the mediation path. The green place, however, has no direct or indirect effect on GPB. Moreover, green trust strengthens the positive relationship between attitude towards green purchase and GPB. The study provides insight to government officials, organisations, and practitioners to comprehend the underlying factors influencing green purchase behaviour.